(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
In recent years, Uzbekistan has made substantial progress in promoting green and sustainable economic transformation. The government’s “Green Economy Strategy for 2030” outlines ambitious goals to reduce energy intensity, expand renewable energy capacity, and ensure environmental safety[1]. Within this framework, commercial banks are expected to play a pivotal role in mobilizing private investment toward low-carbon and climate-resilient projects.[2] [1] Republic of Uzbekistan. (2022). Decree of the President of the Republic of Uzbekistan No. PQ–4477 “On the Strategy for the Transition of the Republic of Uzbekistan to a Green Economy for 2030”. Tashkent. [2] World Bank. (2023). Uzbekistan Country Climate and Development Report. Washington, DC: World Bank Group.